Knowledge, attitude and practice towards sexual and reproductive health including comprehensive sexuality education among first year students of university Malaysia Sabah (UMS), Malaysia - San San Win; Helen Benedict Lasimbang; Mie Mie Cho Win; M Tanveer Hossain Parash; Sai Nay Lynn Aung; Yeap, Boon Tat; Than Myint (2020)
This study aims to assess knowledge, attitude and behavior in sexual and reproductive health (SRH) including comprehensive sexuality education (CSE) among 439 first year students; 213 sciences and 226 arts students from 5 Faculties of University Malaysia Sabah (2016-2017). Exposure of Malaysian students to sexual education is limited to science subjects which are only being taught at upper elementary and secondary high school levels. Arts students are less exposed to sexual education across Malaysia as it is delivered in Basic Science subject only. It was a university-based, cross-sectional, descriptive study. Pretested self- administered questionnaire was anonymously completed by all participants and was conducted from November 2016 to January 2017. Students’ demographic characteristics from Science and Arts streams were same except females, Sabah ethnics and Malays were more in Arts. Awareness of HIV/AIDS, Condom, Wet dream, COC pills and abortion services were more in Science students and statistically significant. 34.3 % and 81.2% of Science students agreed that CSE should be introduced in primary and secondary school but not statistically significant. 22 out of 439 students were sexually active. Science students had more knowledge about SRH and favourable attitude towards sexuality education but less favourable behaviour of watching and reading pornographic materials. It was concluded that there were gaps in knowledge, attitude and behaviour of SRH and need to remedy these by giving appropriate CSE classes to first-year university students in an elective module according to their culture and religious beliefs in accord with International Technical Guidance on Sexuality Education (ITGSE).